(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Further records on Hymenoptera parasitoids of leafminers infesting cultivations, spontaneous or ornamental plants. The Authors give data on the parasitoids bred from Chrysoesthia sex guttella (Thunberg), Chromatomyia syngenesiae (Hardy), Chromatomyia horticola (Gour.) Liriomyza bryoniae (Kaltenbach), Liriomyza sp ., Phytomyza conyzae Hendel, Phytomyza philly reae Her, Phyllonory ct er corylifoliella (Hiibner), Tra chyspygmaea F. , M etriochroa latifoliella (Miller), Monarthropalpus buxi (Lab.). Such species of parasitoids are here reported in accordance to the up recorded list of hosts: Telenomus sp . plus two unidentified Braconidae species; Diglyphu s sp. (A) and (B) ; Diglyphus sp . (A); Semiela cher petiolatus (Girault) ; Apotetrastichus postmarginalis (Boucek) ; Ent edonina e sp . (A) ; Braconidae sp. (A); iglyphus sp. (A); Apotetrastichus sp ; Digl yphus sp. (A) and (B) ; S. petiolatus ; Closte ro ce rus sp (A) ; Cirrospilus pulcher Masi ; Quadrastichus anysis (Walker) ; Tor ymus prope sarothamni Kieffer; Diglyphus sp. (A) and (B); Entedoninae sp . (A) ; Braconidae sp . (B); Cloterocerus sp (A) ; Pediobius sp. and A. postmarginalis, Minotetrastichus sp.; Pholetesor circumscriptus (Nees ), Sympiesis sericeicomis (Nee s), Chromatomyia sp. , Braconidae sp. (A).